7Li(n,) 8Li, 7Be(p,) 8B, 8Li(n,) 9Li AND 8B(p,) 9C REACTIONS OF RADIATING CAPTURE - Sakhiev, S. (Recent Contributions to Physics, 2008)
The given thesis introduces the calculations on the sections of a formalism of radiating capture cuts of 7Li(n,) 8Li и 7Be(p,) 8B, 8Li(n,) 9Li and 8B(p,) 9C reactions which are essential for nuclear astrophysics. Thus wave functions of 8Li, 8B, 9Li и 9C non stable nuclear in three cluster models we have viewed earlier.